Nanoplate-based digital PCR for highly sensitive pork DNA detection targeting multi-copy nuclear and mitochondrial genes - Mokhtar, Nur Fadhilah Khairil; Shun, Ying Quah; Raja Nhari, Raja Mohd Hafidz; Mohamad, Nurhidayatul Asma; Shahidan, Nur Maisarah; Warsanah, Irwan Hanish; Mohd Hashim, Amalia (Taylor and Francis, 2024)
The inclusion of ingredients derived from pigs in highly processed consumer products poses a significant challenge for DNA-targeted analytical enforcement, which could be overcome by using digital PCR. However, most species detection methods use digital PCR to target single-copy nuclear genes, which limits their sensitivity. In this work, we examined the performance of a nanoplate-based digital PCR method that targets multi-copy nuclear (MPRE42) and mitochondrial (Cytb) genes. Poor separation of positive and negative partitions, as well as a ‘rain effect’ were obtained in the porcine-specific MPRE42 assay. Among the optimization strategies examined, the inclusion of restriction enzymes slightly improved the separation of positive and negative partitions, but a more extensive ‘rain effect’ was observed. The high copy number of the MPRE42 amplicon is hypothesized to contribute to the saturation of the positive signal. In contrast, the porcine-specific Cytb assay achieved perfect separation of positive and negative partitions with no ‘rain effect’. This assay can detect as little as 0.4 pg of pork DNA, with a sensitivity of 0.05 (w/w) in a pork-chicken mixture, proving its applicability for detecting pork in meat and meat-based products. For the MPRE42 assay, potential applications in highly degraded products such as gelatin and lard are anticipated.